As influências religiosas e educativas da igreja evangélica luterana de Angola no seu contexto ontem e hoje - Ndawanapo, Tomás (2009)
This work makes an analysis on involvement from the beginning of the Evangelical Lutheran confession with children s education school in Angola. The first part makes an education approach of children, starting from the traditional and culture of Bantu people in Angola. This part includes gestation, childhood, adolescence and rites of passages for girls and boys. The implantation of the church in Angola elapses in simultaneous with the fixation of the colonialism system. Therefore the education plan of the church was subordinated under pretensions of colonialism system. The second part analysis how, the Evangelical Lutheran mission in Angola, valued the children s school education. In this part, is spoken loudly about the catechism from the reform of the church in Germany until the appearance of the Lutheran Church in Angola. This is, also, a part of the work that is touching in the historical point of view, because it brings to the unstressed histories of people, that were arrested and another died because of the implantation of the Lutheran Church in Angola. It is noticed that the colonial system offered to the Angolan people mainly to those that had as eclesial option the Lutheran confession a church, a language for teaching and prison or death for the reticent. The third part and the last one speeches on the evangelical Lutheran church of Angola in it s relevance for children s education. It is showing that Christian Education starts from Jesus Christ s Great Commission in Mathew 28.19-20. It approaches on the children in the Bible, the child s relationships with the modern family in Angola, showing how the Lutheran confession values the children s school education and finishing with a proposal of an education project of IELA that is a challenge. The work starts with a brief introduction and ends with a synthetic conclusion.